Arquitetura de plantas de soja: interceptação de radiação solar, deposição de produtos fitossanitários e produtividade - Müller, Mariele (2017)
The growth of plants depends on the conversion of light energy into chemical energy. The interception photosynthetically active radiation (IPAR) is a function between the leaf area index (LAI) and the extinction coefficient (k). Besides the leaf area, this process also interferes with the architectural distribution of leaves in the vegetative canopy. Excessive growth of plants and their type of architecture may impair the efficiency of agrochemical applications, with low deposition of the active principle in the lower part of the plants. Thus, the present study objected to evaluate if different architectural characteristics of soybean plants influence the interception of solar radiation, phytosanitary management and crop productivity. Four soybean cultivars with different architectural characteristics were evaluated, being BMX Ativa RR, NA 5909 RG, 95R51 and BMX Potência RR. The experiment was conducted in the crops of 2015-2016. The architectural components of the plants and the efficiency of interception of solar radiation, the heliotropic movements of the leaflets and the deposition of drops of phytosanitary products were evaluated. The experiment was a randomized complete block design with five replications. The cultivars presented plants with different architectures among them, reaching 40% difference in height, 61% and 72% in the number and length of branches, respectively. The leaf dimensions varied around 20% and the LAI varied 40% among the cultivars. The intRFA in the lower strata of the vegetative canopy during the day in the reproductive stages was a maximum of 5.16% of the solar radiation that arrived on the vegetative canopy for the 95R51 cultivar. Consequently, it was the cultivar that produced the most in the lower third, with effective fruiting of 22% in the lower third of the plants. The cultivars presented greater number of diaheliotropic movements in the V6 stage compared to the R4 stage. The cultivar 95R51 was the cultivar that obtained higher deposition of droplets in the lower third. At 14h, it was observed greater deposition of droplets and cover in the lower third of the plants due to the position of the leaflets at that time. T hus, plants with lower shoot growth showed greater interception of solar radiation and deposition of phytosanitary products inside the vegetative canopy, resulting in higher yields of grains